EXPLORING THE LANDSCAPE OF JOB CRAFTING IN TEACHER EDUCATION: A SYSTEMATIC REVIEW - Aysun Dağtaş; Senem Zaimoğlu; Fatma Toköz (Novìtnâ Osvìta)
This study focuses on the positive role of job crafting, which is basically adjusting practices to best suit the needs of the employee and the stakeholders. Specifically, in the educational sector, job crafting has been an under-researched area of inquiry; therefore, some of its effects and potential for positive interventions are still being reviewed. With the teaching environment constantly changing over time due to developments in technology and movement toward globalization in the United States, there have been requirements for teachers to job craft—that is, craft their jobs according to the demands of new roles. The following research explicates how job crafting could be regarded as one of the positive ways through which the well-being and motivation of teachers may be increased, impacting student outcomes positively in turn. It will explore how teachers perceive their roles and how job crafting is undertaken within schools. The literature shows that job crafting has positive results and that allowing educators some degree of autonomy and collaboration to meet new demands is essential and must be addressed in teacher education programs.